PENGARUH KEBERAGAMAN GENDER DAN UKURAN DEWAN DIREKSI TERHADAP PENGHINDARAN PAJAK YANG DIMEDIASI OLEH KINERJA KEBERLANJUTAN: THE EFFECT OF GENDER DIVERSITY AND SIZE OF BOARD OF DIRECTORS ON TAX AVOIDANCE MEDIATED BY SUSTAINABILITY PERFORMANCE - Jessyca, Jessyca; Hendi, Hendi; Krisyadi, Robby (Universitas Riau, 2024)
State revenue from taxation is Indonesia's largest source of revenue as evidenced in 2018, where tax revenue contributed 78.1% of total state revenue. However, this is inversely proportional for companies where taxes are a relatively significant expense for companies. This is considered to be able to reduce profits relatively significantly so that tax management efforts are made so that companies can pay taxes, as little as possible. This study aimed to investigate the impact of gender diversity and board size on corporate tax avoidance practices. Additionally, it sought to contribute to the existing body of literature by examining the role of a mediator, specifically sustainability performance, in mediating the relationship between board size, board gender diversity, and tax avoidance in Indonesia. The research analyzed data from all companies listed on the IDX that met the predetermined sample criteria. The findings of this study indicate that neither board size nor board gender diversity has a significant influence on tax avoidance. However, when tested with a mediating variable, namely sustainability performance, both board size and board gender diversity demonstrate a positive effect. Nevertheless, the results of the mediation of sustainability performance are not statistically significant